Intrinsic strengthening and toughening in hexagonal boron nitride by ripples. (1st May 2022) - Lahkar, Simanta; Jeong, Byeongyun; Wang, Xiaodong; Hemker, Kevin; Reddy, Kolan Madhav
Abstract: Increasing strength (maximum stress until permanent deformation) and toughness (fracture resistance) is crucial in engineering applications for all materials, but improving strength often lowers the material's capacity to deform without fracturing, and vice versa. This conflict passes on uniquely to layered van der Waals materials, which are generally brittle. Here, we report simultaneous strengthening and toughening of monolayer and multilayer hexagonal boron nitride (hBN) by ripples. We show using atomistic simulations that stable ripples of varying sizes, modelled based on our experimental observations, increase the intrinsic crack nucleation toughness of hBN by improving both fracture strain and bond strength through a distortion-mediated mechanism. This effect has been traced to the extent of structural asymmetry at the onset of failure, revealing a potential strategy to bolster the fundamental fracture and strength properties of single-phase van der Waals materials significantly. Graphical Abstract: Graphical Abstract Image, graphical abstract .